Growth and electrical transport of germanium nanowires - KRSTIC, VOJISLAV (American Institute of Physics, 2001)
Single crystalline germanium nanowires have been synthesized from gold nanoparticles based on a vapor-liquid-solid growth mechanism. Germanium powder was evaporated at 950?C, and deposited onto gold nanoparticles at 500?C using argon as a carrier gas. The diameter of the germanium nanowires ranged from 20 to 180 nm when gold thin films were utilized as the substrate, while the nanowires grown from 10 nm Au particles showed a narrower diameter distribution centered at 28 nm. The growth direction of germanium nanowires is along the [111] direction, determined by high resolution transmission electron microscopy. Transport measurements on individual Ge nanowires indicate that the wires are heavily doped during growth and that transport data can be explained by the thermal fluctuation tunneling conduction model.
PUBLISHED
Keywords: Physics